HIV Status Disclosure through Family-Based Intervention Supports Parenting and Child Mental Health in Rwanda - Chaudhury, Sumona; Kirk, Catherine M.; Ingabire, Charles; Mukunzi, Sylvere; Nyirandagijimana, Beatha; Godfrey, Kalisa; Brennan, Robert T.; Betancourt, Theresa S. (Frontiers in Public Health, 2016)
Introduction: Few evidence-based interventions exist to support parenting and child mental health during the process of caregiver HIV-status disclosure in Sub-Saharan Africa. A secondary analysis of a randomized-controlled trial was conducted to examine the role of family-based intervention versus usual social work care (care as usual) in supporting HIV status disclosure within families in Rwanda. Method: Approximately forty households were randomized to family-based intervention and forty households to care as usual. Parenting, family unity and child mental health during the process of disclosure were studied using quantitative and qualitative research methods. Results: Many of the families had at least one caregiver who had not disclosed their HIV status at baseline. Immediately post-intervention, children reported lower parenting and family-unity scores compared to those in the usual care group. These changes resolved at three-month follow-up. Qualitative reports from clinical counselor intervention sessions described supported parenting during disclosure. Overall findings suggest adjustments in parenting, family unity, and trust surrounding the disclosure process. Conclusion: Family-based intervention may support parenting and promote child mental health during adjustment to caregiver HIV status disclosure. Further investigation is required to examine the role of family-based intervention in supporting parenting and promoting child mental health in HIV status disclosure.